Comparison of Speech Recognition and Localization Ability in Single-sided Deaf Patients Implanted With Different Cochlear Implant Electrode Array Designs. Issue 1 (January 2021) - Speck, Iva; Ketterer, Manuel Christoph; Arndt, Susan; Aschendorff, Antje; Jakob, Till F.; Hassepass, Frederike
Abstract : Objective: Choice of electrode array (EA) design and differences in outcome are major concerns both to patients with single-sided deafness (SSD) and to surgeons before cochlear implant (CI) surgery. The present work investigates the effects of EA design on 1) insertion depths, and 2) audiological outcomes of SSD CI recipients. Study Design: Retrospective study. Setting: Tertiary academic center. Patients: Forty patients with acquired SSD matched according to duration of deafness Main Outcome Measures: Fourteen CI recipients were implanted with a perimodiolar electrode (cochlear perimodiolar [CPM]), 12 with a shorter lateral wall electrode (cochlear lateral wall [CLW]), and 14 with a longer lateral wall electrode array (medEl lateral wall [MLW]). Postoperative rotational tomography was evaluated to determine cochlear size and EA angle of insertion depth (AID). Binaural speech comprehension in noise (in three configuration presentations) and localization ability were assessed 12 months postoperatively with CI. Results: AID was significantly deeper in MLW (mean 527.94 degrees) compared with the CPM (mean 366.35 degrees) and CLW groups (mean 367.01 degrees). No significant difference in AID was seen between the CPM and CLW groups (difference 0.66 degrees). Cochlear sizes revealed no significant differences between any groups. All three groups showed significant improvement in head shadow effect (difference on average CPM: 6.3 dB SPL, CLW 5 dB SPL, and MLW 4.05 dB SPL) and localization ability at 12 months postoperatively (difference on average CPM: 19.72 degrees, CLW: 24 degrees, and MLW: 12.9 degrees). No significant difference in the extent of audiological benefit was observed between any groups. Conclusion: No effect on binaural benefit was apparent from the selection of the three EA designs in SSD CI recipients. Further studies focusing on subjective results, sound quality, and music perception depending on EA design in SSD CI recipients are needed. Abstract : Supplemental Digital Content is available in the text